Analisis Preskriptif Hukum Ekonomi Syariah terhadap Praktik Pengenaan Biaya Administrasi QRIS pada Usaha Mikro - Purwono, Muhammad Azhar Firdaus; Dzakir, Muhammad Najwan; Fuad, Hanif Jayidul; Imtiyaz, Mohammad Alqis Fawwazil; J, Jaenudin; Herdiana, Dian (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the appropriateness of charging administrative fees in digital payment transactions using QRIS among micro-enterprises in light of the regulations of Bank Indonesia and the principles of Islamic economic law (sharia). Using a qualitative method with a prescriptive approach, this research evaluates whether such practice is right or wrong based on interview data from merchants and consumers, as well as a literature review related to digital payment systems, MDR regulation, and fiqh muamalah. The analysis finds that merchants’ imposition of QRIS administrative fees constitutes conduct that is not aligned with regulatory provisions, violates consumer protection principles, and contradicts the principles of fairness, transparency, and the concept of ‘iwadh in muamalah. The findings affirm that QRIS administrative fees are invalid both from a regulatory and sharia perspective, thereby necessitating stronger education and oversight to ensure fair and sharia-compliant digital transaction practices.